Primary actinomycotic lung abscess. Issue 841 (November 1995) - Mohan, A; Chattopadhyay, TK; Sharma, SK; Dinda, AK; Sharma, R
Abstract : A case of recurrent massive haemoptysis in whom primary actinomycotic lung abscess was diagnosed following right pneumonectomy is reported.